Semântica cognitiva aplicada: a radialidade da categoria RELIGIÃO nos discursos dos imigrantes italianos (de 1875 à década de 1950) - Granzotto, Carina Maria Niederauer (My University, 2014)
This dissertation has the goal of reconstructing the cognitive cultural models that made up the conceptual category RELIGION, with a basis on the discourse of/about immigrants from the Old Italian colonies from the northern region of Rio Grande do Sul, in relation to how they experienced religiosity. This is done through a semantic analysis of the expressions used, for instance, in the texts of anthropologic and historiographic nature; reports of memories, letters, and diaries. The sources of this discourse are documented bibliographies that cover the period from 1875 to the decade of 1950. The corpus of this work is made up of 138 segments, organized accordingly into five categories with different sources. The investigation centers on the field of Cognitive Semantic, oriented by the Theory of Idealized Cognitive Models (TICM), proposed by Lakoff and his colleagues. This study justifies itself and guarantees its unprecedented nature since there has not yet been empirical studies done about religion in a culture or sub culture. The theory presented allows the evaluation of how a conceptual category structures itself and evolves in a culture. The analysis takes place inside the sphere of Catholic Religion, since this is the religion that predominates the culture in question. The method utilized is the hypothetic-deductive, from which the preliminary radial structure of the category is built, with a basis on the inspectional analysis of the initial corpus. The hypotheses is that: (1) the category has a structure that is propositional radial, in which the prototypical sub-models are RITUALS; (2) the category RELIGION has a radial structure having GOD as a radial axis and FATHER as the prototypical center; (3) metaphoric and metonymic structures organize extensions or projections from these rays; (4) the types of propositional structures, like the propositional model script, organize elements that make up the radial structure. The Moral Metaphor System is applied as a model that organizes this structure. The analyses of the selected corpus confirm the initial hypotheses suggested. The sub model RITUALS is confirmed as the one which prototypically represents the category. The other hypotheses confirmed concerns the influence of the propositional model script as the integral part of the RITUALS model. The preliminary hypothetic radial structure, at the end of the analyses, is adjusted to the findings of the research. This investigation does not aim to bring up conceptions of religion but rather to investigate the semantic-conceptual structure of RELIGION through the explicit codification reveled in linguistic expressions or in inferences from them, as well as through metaphoric, metonymic, and propositional models.
Esta dissertação tem por objetivo reconstruir os modelos cognitivo-culturais que estruturam a categoria conceitual RELIGIÃO, com base nos discursos dos/sobre os imigrantes das antigas colônias italianas na região Nordeste do estado do Rio Grande do Sul, relativamente ao modo como esses experienciavam a religiosidade. Isso se dá a partir de uma análise semântica dos enunciados presentes, por exemplo, em textos de natureza antropológica, historiográfica; relatos de memórias, cartas e diários. As fontes desses discursos são documental-bibliográficas e cobrem o período de 1875 à década de 1950. O corpus é constituído de 138 segmentos discursivos, organizados de acordo com cinco categorias diferentes de fontes. A investigação situa-se no campo da Semântica Cognitiva, orientada pela Teoria dos Modelos Cognitivos Idealizados (TMCI), proposta por Lakoff e seus colaboradores. Esse trabalho se justifica uma vez ainda não existirem estudos empíricos sobre a religião em uma cultura ou subcultura sob o viés da Semântica Cognitiva, garantindo seu caráter inédito. Essa teoria permite avaliar como uma categoria conceitual se estrutura e evolui em uma cultura. A análise empreendida dá-se dentro da esfera da Religião Católica, uma vez ser esta a religião predominante na cultura em questão. O método utilizado é o hipotético-dedutivo, a partir do qual se constrói a estrutura radial preliminar da categoria, com base numa análise inspecional do corpus inicial. Tem-se por hipóteses que: (1) a categoria tem uma estrutura proposicional radial, cujo submodelo prototípico é RITUAIS; (2) a categoria RELIGIÃO estrutura-se basicamente por radialidade, tendo como eixo-de-raio DEUS, com centro prototípico em PAI; (3) estruturas metafóricas e metonímicas organizam extensões ou projeções a partir desses raios; (4) tipos de estruturas proposicionais, como o modelo proposicional script, organizam elementos constitutivos da estrutura radial. O Sistema da Metáfora Moral é aplicado como um modelo organizador dessa estrutura. A análise do corpus selecionado confirma as hipóteses inicialmente levantadas. O submodelo RITUAIS é confirmado como o que prototipicamente representa a categoria. Outra hipótese confirmada é a da influência do modelo proposicional script, como parte integrante do modelo RITUAIS. A estrutura radial hipotética preliminar, ao final das análises, é ajustada aos achados da pesquisa. Esta investigação não visa levantar concepções de religião, mas investigar a estrutura semântico-conceitual de RELIGIÃO por meio da codificação explícita revelada em expressões lingüísticas ou em inferências a partir delas, por meio de modelos metafóricos, metonímicos e proposicionais.
Keywords: Liguistica; Semântica cognitiva; Modelos cognitivo-culturais; Teoria dos Modelos Cognitivos Idealizados; Categoria religião; Modelo proposicional radial; Imigrantes italianos; Discurso; Análise semântica; Cognitive semantic; Cognitive cultural models; Theory of Idealized Cognitive Models; Religion category; Propositional radial model; Italian immigrants; Speech; Semantic analysis